Źródła zróżnicowań rozwoju społeczno-ekonomicznego w krajach wysoko rozwiniętych na przełomie XX i XXI w. - Pięta-Kanurska, Małgorzata (The Sources of Differentiation of Socio-Economic Development Process in High Developed Countries at the End of 20th and the Beginning of 21st Century, 2005)
Conducted researches in the range of spatial economy show the problem of existing and increasing of socio-economic disproportions in the world economy. This situation brings many unfavourable implications for functioning of global and also national economies. That is why in the article there is taken an attempt to give an answer about sources and mechanisms of shaping this disproportions, and also about perspectives for this process in the future.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 170-177